2007
DOI: 10.3844/jssp.2007.202.207
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Employability Skills of Technical-Vocational Students in Malaysia

Abstract: Technical-Vocational Education and Training (TVE) system plays important role in providing highly skilled workforce to fulfill the needs of industries. An empirical research of TVE system is necessary to identify effective TVE system to successfully equip students with technical skills that would enable them to fulfill the current work demands and professional expectations. The objective of this paper is to present the findings of TVE system implementation in one of the technical training institution in Malays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 6 publications
3
22
3
Order By: Relevance
“…However, the mean was lower than the findings of Kazilan et al (2009) and of Bakar and Hanafi (2007), which found that the mean employability skill scores of Malaysian vocational trainees was 3.86 and 3.8, respectively. The results of this study show no significant difference in employability skills as a function of gender.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…However, the mean was lower than the findings of Kazilan et al (2009) and of Bakar and Hanafi (2007), which found that the mean employability skill scores of Malaysian vocational trainees was 3.86 and 3.8, respectively. The results of this study show no significant difference in employability skills as a function of gender.…”
Section: Discussioncontrasting
confidence: 70%
“…The Cronbach's alpha reliability estimate of the instrument to measure employability skills was 0.85. This was lower than the reliability estimate of 0.95 obtained by Kazilan et al (2009) and 0.96 by Bakar and Hanafi (2007).…”
Section: Research Instrumentcontrasting
confidence: 64%
See 2 more Smart Citations
“…This may be because PISA is an assessment of students' ability to solve problems focused on real-life applications, which tends to be more difficult for students to master (Clarke, 2016). The results support the work of other studies for example, the one linking the lack of problem-solving skills to TVET graduates (Bakar & Hanafi, 2007;Department of Community College Education, 2011;Mimi Mohaffyza Mohamad, Yee Mei Heong, Nurfirdawati Muhammad Hanafi, & Tee Tze Kiong, 2014;Rahman, Mokhtar, Hamzah, & Yasin, 2011;Sander, 2012;Zaliza Hanapi, Mohd Safarin Nordin, & Khamis, 2015). In accordance with the present findings, previous studies, as noted above, have also demonstrated that these are valid concerns because employees with strong communicative skills, ability to perform tasks and who were highly critical and able to solve problems were more sought after and not just those who possessed technical skills (Deutsch et al, 2009;Lin & Cherng, 2006;Müller et al, 2009;Young & Chapman, 2010).…”
Section: Discussionsupporting
confidence: 89%